Reconstructing high-quality large-scale metabolic models with merlin - Dias, Oscar (2018)
Here the basic principles of reconstructing genome-scale metabolic models with merlin are described. This tool covers the basic stages of this process, providing several tools that allow assembling models, using the sequenced genome as starting point. merlin has two main modules, separating the process of annotating (enzymes, transporters and compartments) on the genome from the process of model assembly, though information from the former is integrated in the latter after curation. Moreover, merlin provides several tools to curate the model, including tools for generating reactions gene rules and placeholder entities for biomass precursors, such as proteins (e-protein) or nucleotides (e-DNA and e-RNA) amongst others. This tutorial covers each feature of merlin in detail, including the assessment of experimental data for validation of the model.